EVALUATION OF CHRONIC KIDNEY DISEASE PATIENTS FOR INSULIN RESISTANCE IN TERTIARY CARE HOSPITAL: Chronic Kidney Disease & Insulin Resistance - Tahir, Dr Sufyan; Hayat, Asma; Khan, Saleem Ahmed; Ahmad, Tariq Mahmood; Rehman, Saqibah; Majeed, Numan (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate the patients of chronic kidney disease for insulin resistance. Study Design: Cross sectional observational study. Place and Duration of Study: The study was conducted in the chemical pathology department of Army Medical College/Military Hospital Rawalpindi, from Nov 2016 to Apr 2017. Material and Methods: Fifty patients were recruited for this study with deranged renal functions and/or having any structural renal abnormality for more than 3 months. These patients did not have any history of diabetes and dialysis. Fifty ages matched healthy individuals were included as controls. Renal function tests, lipid profile, complete blood count, fasting plasma glucose and serum insulin levels were performed in all subjects. Insulin resistance was calculated by using homeostatic model for assessment of insulin resistance (HOMA-IR). Results of this study were analyzed on SPSS version 23. Results: Fasting insulin levels were much higher in the patient with chronic kidney disease as compared to controls (p-value=0.001). HOMA-IR in cases was also significantly higher. Statistical comparison of lipid profile showed significant difference of only triglycerides level. Conclusion: HOMA-IR is markedly raised in the patients of chronic kidney disease. This indicates a significant association of chronic kidney disease with insulin resistance.